Adaptive guidance for low-thrust formation flight mission in Circular Relative Orbit - Ruggiero, Dario; Ito, Takahiro; Capello, Elisa; Tsuda, Yuichi (Acta astronautica, 2025)
Spacecraft formation flight is increasingly pivotal in the design of new space missions. This demands an high level of autonomy to optimize science time, and the development of advanced mission concepts to surpass current technological limitations. Recently, Low Earth Orbit (LEO) has been explored as solution for experimental validation of novel formation flight technologies. LEO is related to proximity formation flight missions, which require active guidance algorithms to ensure mission success and safe operations. An efficient guidance algorithm is proposed to enhance the autonomy of proximity formation flight missions, enabling variable formations and reconfiguration while ensuring safety. The optimal formation trajectory problem, conceptualized as Circular Relative Orbit, addresses the relative motion with respect to a reference orbit. Rigorous Lyapunov design is proposed to ensure convergence to the desired trajectory, guaranteeing closed-loop system stability. It incorporates an Artificial Potential Field function to deal with the formation flight problem. Initial simulations are conducted to assess the effectiveness of the proposed approach within the restricted Two-Body dynamics framework. The algorithm is applied to accomplish a space interferometer deploying mission in LEO, demonstrating its efficacy through a compact implementation. Finally, the algorithm’s general and wider effectiveness is validated with elliptical and L2 Halo reference orbits. •Formation flight framework for missions in Earth Orbit.•Guidance and control of spacecraft in Circular Relative Orbit.•Autonomous space-interferometer deploying mission in Earth Orbit.•Accurate formation control in Circular, Elliptic, and L2 Halo reference orbits.